Rancang Bangun Aplikasi Administrasi Akademik Dan Kemahasiswaan (AAK) Berbasis Web Pada STIKES Surabaya - Cahyaningasri, Berlita Tri; Tanuwijaya, Haryanto; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
STIKES Surabaya is one of the Health Sciences College which has three major of study, there are S1 Nutritional Sciences program, S1 of Nursing program and also D3 of Midwife program. The problem side AAK in STIKES Surabaya is still using Microsoft Excel to manage schedules, and class space, presence and assessment of student attendanced every semester. So that often to happen a duplication of data at the time of inputting the data, causing double date. In another side, data entry errors often occurs that makes the information provided is not equal with the information get. In the part of AAK there is only one person to input all the transaction that need to take a long time.Based on the that issues, then made AAK application based on web. This application can create a schedule of courses, attendance precense and grades assessment of the students. So it can help you achieve in a decision-making system for the processing of data, information and good service.This application can KRS process so that students can see the semester each academic year. Other than that, provide KRS report, lectures attendaces, students attendances, student assessment and also find out the schedule of lectures online, so the students, lectures and AAK can access these application where ever and whenever.Keywords: Perwalian, Presensi, Penjadwalan Kuliah, STIKES Surabaya.